The Green Goddess: William Archer's Great War Play. Issue 2 (November 2013) - Kelly, Veronica
William Archer's melodrama The Green Goddess (1919) is the sole commercial international success enjoyed by the famed theatre critic and Ibsen scholar. While it successfully applies its author's knowledge of the conventions of popular melodrama, the play's subject 'foundrsquo; its author in late 1919 during a period of heightened post-war personal and public turmoil. Set in a fictional principality on the North-West Frontier of imperial India, it takes the form of a hostage drama whose principal character is the cynical and ruthless Raja, played in the theatre and in two films by the veteran character actor George Arliss. This annotated edition uses staging evidence from the Promptbook of the 1924 Australian commercial production by J. C. Williamson Ltd and the silent (1923) and sound (1930) films. The Introduction places The Green Goddess in the generic context of post-war Orientalism. It explores its origins in Archer's official war work refuting German propaganda in various pamphlets and dramas. His wartime polemical themes of 'barbarismrsquo; and 'civilisationrsquo; (especially relating to Belgium) also permeate his 1919 play. The ethics of the aerial terror bombing of civilians, practised routinely in colonial policing and introduced to Europe in the Great War, both resolve the action of The Green Goddess and interrogate former wartime moral polarities. Its staging details are sourced in Archer's India and the Future (1917), such that an early example of British theatre dealing with the trauma of the Great War is overlaid upon a conventional-seeming colonial adventure melodrama.